Bone marrow MRI after autologous transplantation and the effect of residual tumor on progression-free survival of multiple myeloma patients - M. V. Solovev; L. P. Mendeleeva; G. A. Yatsyk; N. S. Lutsik; M. V. Firsova; E. G. Gemdzhian; V. G. Savchenko (Онкогематология, 2019)
Background . The study of influence of residual tumor mass, determined by magnetic resonance imaging (MRI), on the progression-free survival (PFS) remains an actual problem. Since the visual assessment of tumor bone marrow lesion can be one of the criteria for the subsequent personalized treatment choice in multiple myeloma patients.The objective of study was to determine the effect of bone marrow lesions detected by MRI after autologous hematopoietic stem cells transplantation (auto-HSCT) on PFS in multiple myeloma patients.Materials and methods . The prospective study included 60 patients who underwent spine and pelvic bones MRI on the 100 th day after autoHSCT.Results . Focal bone marrow changes were found in 47 of them – from 1 to 56 lesions (mean 6 ± 9). Significant (p = 0.01) differences of PFS in multiple myeloma patients depending on the presence or absence of tumor mass on 100 th day after auto-HSCT were revealed: with MRI negative status, 2-year PFS was 89 % versus 50 % in a group of patients with residual tumor mass.Conclusion . MRI-negative status after auto-HSCT is a favorable prognostic factor contributing to prolonged disease-free survival.